Molecular detection and phylogenetic analysis of Hepatozoon spp. in questing Ixodes ricinus ticks and rodents from Slovakia and Czech Republic - Hamšíkova, Zuzana; Silaghi, Cornelia; Rudolf, Ivo; Venclíková, Kristýna; Mahríkova, Lenka; Slovák, Mirko; Mendel, Jan; Blažejová, Hana; Berthová, Lenka; Kocianová, Elena; Hubálek, Zdeněk; Schnittger, Leonhard; et al. (2017)
By amplification and sequencing of 18S rRNA gene fragments, Hepatozoon spp. DNA was detected in 0.08 % (4/5057) and 0.04 % (1/2473) of questing Ixodes ricinus ticks from Slovakia and Czech Republic, respectively. Hepatozoon spp. DNA was also detected in spleen and/or lungs of 4.45 % (27/606) of rodents from Slovakia. Prevalence of infection was significantly higher in Myodes glareolus (11.45 %) than in Apodemus spp. (0.28 %) (P < 0.001). Sequencing of 18S rRNA Hepatozoon spp. gene amplicons from I. ricinus showed 100 % identity with Hepatozoon canis isolates from red foxes or dogs in Europe. Phylogenetic analysis showed that at least two H. canis 18S rRNA genotypes exist in Slovakia of which one was identified also in the Czech Republic. The finding of H. canis in questing I. ricinus suggests the geographical spread of the parasite and a potential role of other ticks as its vectors in areas where Rhipicephalus sanguineus is not endemic. Sequencing of 18S rRNA gene amplicons from M. glareolus revealed the presence of two closely related genetic variants, Hepatozoon sp. SK1 and Hepatozoon sp. SK2, showing 99–100 % identity with isolates from M. glareolus from other European countries. Phylogenetic analysis demonstrates that 18S rRNA variants SK1 and SK2 correspond to previously described genotypes UR1 and UR2 of H. erhardovae, respectively. The isolate from Apodemus flavicollis (Hepatozoon sp. SK3b) was 99 % identical with isolates from reptiles in Africa and Asia. Further studies are necessary to identify the taxonomic status of Hepatozoon spp. parasitizing rodents in Europe and the host-parasite interactions in natural foci.